Metabolite profiling of heat treated whole palm oil extract - M.F., Akhmazillah; M. R., Sarmidi; L., S. Chua (2011)
The chemically complex and diverse nature of the plant metabolome require different platform technology to entire range of metabolites. An ultra-performance liquid chromatography-electrospray ionization tandem mass spectrometry (UPLC-ESI-MS/MS) technique was developed to profile and identify a set of small-molecule metabolites found in heat treated whole palm oil extract. An investigation was carried out on the effect of heat treatment on the yield, quality and metabolites profile for whole palm oil extract. Palm fruits were collected, cleaned and sterilized for 0, 20, 40 and 60 minutes. The kernels were then stripped from the sterilized fruit to get the pulp (mesocarp part) and later the pulp was pressed using small scale expeller. The resulting puree was centrifuged at 4000 rpm for 20 minutes. The results show that there was a significant difference between sterilization time of 0 minute and 40 minutes in yield and quality. Of all, the highest yield of oil of 19.9% was obtained at sterilization time of 40 minutes with DOBI value of 5.95 ± 0.08 and FFA of 1.44 ± 0.10. The MarkerView software version 1.2.0.1 analysis of the UPLC-ESI-MS/MS preliminary experimental data demonstrated the distribution and identity of several compounds in the whole palm oil extract for 40 minutes sterilization and 0 minute of sterilization.